Structural Realism and Institutional Barriers in the UN Security Council's Failure: Israeli-Palestinian Conflict - Agussalim Agussalim; Ariesani Hermawanto; Sucahyo Heriningsih (Journal of Law and Social Politics, 2026)
Background: … Objective: This study examines the failure of the United Nations Security Council (UN) in intervening in the Israeli-Palestinian conflict using a structural realism approach and an analysis of institutional barriers. The focus of the research lies in the role of the geopolitical interests of permanent members of the Security Council who use veto power to block peace resolutions, as well as the weak UN institutional mechanisms in international law enforcement. Methods: A qualitative method with a single case study was used to analyse official documents, Security Council resolutions, and related literature. Results: The study results show that the dominance of national interests and undemocratic institutional structures are the main factors for the failure of interventions. These findings provide important recommendations for UN institutional reform to improve the effectiveness of international peace governance. Conclusion: …